The economic impact of E-commerce - Hoq, Ziaul; Kamal, Md. Shawkat; Chowdhury, A H M Ehsanul Huda (BRAC University, 2010)
E-commerce has a significant impact on business costs and productivity. E-Commerce has a chance to be widely adopted due to its simple applications. Thus it has a large economic impact. It gives the opportunity for “boundary crossing” as new entrants, business models, and changes in technology erode the barriers that used to separate one industry from another. This increases competition and innovation, which are likely to boost overall economic efficiency.